Hacia una reflexion ontologica del arte moderno hondureño: una vision desde la filosofia de Arthur C. Danto - ZUNIGA MEJÍA, Rafael Antonio (2018)
The work will seek to understand how were the origen of modern art in Honduras, analyzing the work of the most renowned artist. For this, the phylosophy and aesthetic visión of Arthur C Danto will be used in order to make and ontology of Honduras art that allows to establish how this has been developed. The objective is to reflecto n the type of lenguage used by contemporany artist in Honduras classifying the work of these artist temporally and identifying each of the proposedstyles from mimetic representation painting, abstract painting, installation and object art.